HARDSHIP AND EASE (USR AND YÜSR) CONCEPTS IN KUR’AN - Abdurrahman ALTUNTAŞ (Fırat University, 2019)
Hardship and Ease (Usr and Yüsr) concepts are among the notions used in Kur’an. The place is given to these two concepts to explain the perception of difficulty and ease. The general framework of the challenges and ease were drawn on the occasion of these two concepts. Life, according to the Kur’an,. has many difficulties. When seen from this perspective it is a challenge in every task. In Kur’anic understanding, the ease is accessible as a result of enduring difficulty. According to the Kur’an, the advent of ease after hardship is a factual situation. The hardship and ease concepts in Kur’an have many means. In general meaning usr notion is used as difficult and hardship; on the other hand, yüsr is used as ease and easiness The use of these concepts in Kur’an catches the eye on many issues such as giving charity, piety, social life, worship life and notification. Because difficulty and ease are a state encountered in all aspects of life. What really matters is ease in terms of the frame of the Quran that has set for these two concepts; yet the hardship is temporary or casual. In this respect, one must put forth an effort to overcome every difficulty encountered. By this effort, the value of an acquired task is much better known. Whereas, the value of a work gained easily is not appreciated. An ease is provided for the person after faith, good deeds and moral According to the Kur’an, whoever have in faith, good deeds and morality an ease is provided for him. This easiness crops up as a result of one’s patience and struggle on right path. But in case of an opposite situation, in other meaning in the event of denying, bad deeds and moral, one faces a hardship. This difficulty or challenge is also a situation that occurs as a result of person’s own choice